Pengaruh Model Pembelajaran Project Based Learning terhadap Keterampilan Proses Sains pada Ta Makanan di Sekitarmu Kelas VIII - Niken Gusti Amanda; Lulu Tunjung Biru; Dwi Indah Suryani (PendIPA Journal of Science Education, 2023)
The background of this research was the lack of practicum activities carried out and the lack of use of project-based learning models that make students feel difficulty understanding material on the theme of food around me and still lack the ability to process science in grade VIII students. This study aimsed to analyze the influence of the food-themed project based learning (PjBL) learning model. Data collection used a quasi-experimental design method, with a nonequivalent control group type. In this design, there were pre-test and post-test for the experimental and control classes. The research instruments applied were test sheets, observations, interviews and validation. The project-based learning model was developed through stages including presenting basic questions, (2) making project plans, (3) scheduling activities, (4) checking students' progress in working on their projects (monitoring), (5) reviewing test results, and (6) evaluation. The results of the study show that the project based learning (PjBL) learning model has an influence on the ability of science processes as indicated by a significance value of 0.002 <0.05 which indicates H0 is rejected and H1 is accepted.